2019
DOI: 10.1523/jneurosci.2565-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Diversity Revealed by Ca2+-Permeable AMPA Receptors at the Calyx of Held Synapse

Abstract: GluA2-lacking Ca 2ϩ -permeable AMPARs (CP-AMPARs) play integral roles in synaptic plasticity and can mediate excitotoxic cellular signaling at glutamatergic synapses. However, the developmental profile of functional CP-AMPARs at the auditory brainstem remains poorly understood. Through a combination of electrophysiological and live-cell Ca 2ϩ imaging from mice of either sex, we show that the synaptic release of glutamate from the calyx of Held nerve terminal activates CP-AMPARs in the principal cells of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 80 publications
(100 reference statements)
3
26
0
Order By: Relevance
“…This particular property of a giant synapse allows the recording of signals that may be present in other synapses but not resolved due to their small amplitude. We (Gonzalez-Inchauspe, Urbano, Guilmi, & Uchitel, 2017), have found that the presynaptic terminal of the brainstem calyx of Held synapse lacks ASIC channels while the MNTB neurons respond to acidification with a transient inward current sensitive to amiloride and to PcTx1(see also Lujan, Dagostin, & von Gersdorff, 2019).We have also shown the absence of these currents in ASIC1a −/− mice suggesting that homomeric ASIC-1a mediate these currents in MNTB neurons. Furthermore, we have detected ASIC1a-mediated currents during synaptic transmission after blocking AMPA and NMDA glutamate receptors, suggesting that an acidification of the synaptic cleft due to the co-release of neurotransmitter and H + from synaptic vesicles is capable of activating ASIC postsynaptic channels.…”
Section: Proton S a S Neurotr An S Mit Ter Ssupporting
confidence: 52%
See 4 more Smart Citations
“…This particular property of a giant synapse allows the recording of signals that may be present in other synapses but not resolved due to their small amplitude. We (Gonzalez-Inchauspe, Urbano, Guilmi, & Uchitel, 2017), have found that the presynaptic terminal of the brainstem calyx of Held synapse lacks ASIC channels while the MNTB neurons respond to acidification with a transient inward current sensitive to amiloride and to PcTx1(see also Lujan, Dagostin, & von Gersdorff, 2019).We have also shown the absence of these currents in ASIC1a −/− mice suggesting that homomeric ASIC-1a mediate these currents in MNTB neurons. Furthermore, we have detected ASIC1a-mediated currents during synaptic transmission after blocking AMPA and NMDA glutamate receptors, suggesting that an acidification of the synaptic cleft due to the co-release of neurotransmitter and H + from synaptic vesicles is capable of activating ASIC postsynaptic channels.…”
Section: Proton S a S Neurotr An S Mit Ter Ssupporting
confidence: 52%
“…Currently, the time course of pH changes at fast synapses has not been measured in detail, but from indirect estimations at ribbon‐type and hippocampal synapses (Du et al, ; Palmer et al, ), it is possible to hypothesize that the synaptic cleft pH waveform is complex, including an acid and alkaline shift with a time course that depends on the buffer capacity of the cleft. The resulting change in extracellular pH is, therefore, likely to be much smaller than at ribbon synapses but sufficient to inhibit AMPA receptors by enhancing desensitization (Lei, Orser, Thatcher, Reynolds, & MacDonald, ; Traynelis & Cull‐Candy, ); and to activate ASICs and generate a postsynaptic current as shown by Du et al () at the amygdala; Kreple et al () at the nucleus accumbens and by our group at the mouse calyx of Held (Gonzalez‐Inchauspe, Urbano, Di Guilmi, & Uchitel, ), confirmed recently by Lujan, Dagostin, and von Gersdorff (), (Figure [left]). Furthermore, cleft pH can also remain acidic during prolonged stimulation or during a variety of pathological conditions such as during epileptic activity.…”
Section: Evidence For Ph Changes In the Synaptic Cleftmentioning
confidence: 75%
See 3 more Smart Citations